Images of Birds in the History of Portuguese Poetry: Features of Metaphorics - Marina V. Kuteva; Varvara A. Makhortova (Studia Litterarum, 2022)
The article offers a review regarding to the metaphorical reinterpretations of lexemes relating to the semantic field “bird” in the best Portuguese poems, whose works are distinguished by continuity and are based on the poetic accomplishments and achievements of those word artists who created their verses in previous eras. The most consequential influence on the moods and figurative system of followers had Francisco Sa de Miranda and Luis de Camoes, which are also briefly described in this work. The results of the study conducted using a complex technique (methods of contextual, semantics and stylistic analysis) testify to the wide figurative and metaphorical potential of ornythonymic vocabulary. In Portuguese poetry, the image of birds is used to convey a variety of meanings, such as “poems,” “creativity,” “I, my soul,” “love,” “hope,” “longing,” “struggle,” as well as “freedom” (bird in general) and “despotism” (vulture).